Trichotorquatus gen. nov. - a new genus of soil cyanobacteria discovered from American drylands1 - Pietrasiak, Nicole; Reeve, Sharon; Osorio-Santos, Karina; Lipson, David A; Johansen, Jeffrey R (Journal of phycology, 2021)
Cyanobacteria are crucial ecosystem components in dryland soils. Advances in describing α-level taxonomy are needed to understand what drives their abundance and distribution. We describe Trichotorquatus gen. nov. (Oculatellaceae, Synechococcales, Cyanobacteria) based on four new species isolated from dryland soils including the coastal sage scrub near San Diego, California (USA), the Mojave and Colorado Deserts with sites at Joshua Tree National Park and Mojave National Preserve, California (USA), and the Atacama Desert (Chile). The genus is morphologically characterized by having thin trichomes (<4.5 μm wide), cells both shorter and longer than wide, rarely occurring single and double false branching, necridia appearing singly or in rows, and sheaths with a distinctive collar-like fraying and widening mid-filament, the feature for which the genus is named. The genus is morphologically nearly identical with Leptolyngbya sensu stricto but is phylogenetically quite distant from that genus. It is consequently a cryptic genus that will likely be differentiated in future studies based on 16S rRNA sequence data. The type species, T. maritimus sp. nov. is morphologically distinct from the other three species, T. coquimbo sp. nov., T. andrei sp. nov. and T. ladouxae sp. nov. However, these latter three species are morphologically very close and are considered by the authors to be cryptic species. All species are separated phylogenetically based on sequence of the 16S-23S ITS region. Three distinct ribosomal operons were recovered from the genus, lending difficulty to recognizing further diversity in this morphologically cryptic genus.
Keywords: deserts; Sequence Analysis, DNA; RNA, Ribosomal, 16S; ekosystém; DNA, Bacterial; sinice; techniky typizace bakterií; Chile; cryptic genera; biological soil crusts; Cyanobacteria; United States; Coastal Sage Scrub; Bacterial Typing Techniques; Atacama Desert; půda; 16S rRNA gene; DNA bakterií; RNA ribozomální 16S; Colorado; cryptic species; polyphasic approach; fylogeneze; Spojené státy americké; sekvenční analýza DNA; 16S-23S ITS; Mojave Desert; Ecosystem; Phylogeny; Soil